The Correlation between Traditional Ultrasound Features and the Expression of Estrogen Receptor, Progesterone Receptor, Human Epidermal Growth Factor Receptor-2, and Ki-67 in Breast Carcinoma - Ping Wang, MM, Junfan Li, Wensheng Yue, MM, Wenyan Li, MM, Yuqun Luo, MM (Advanced Ultrasound in Diagnosis and Therapy, 2018)
Objective: To evaluate the correlation between traditional ultrasound and the expression of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (Her-2), and Ki-67 expression in breast carcinoma.Methods: A retrospective analysis of 400 cases of breast cancer, which were confirmed by pathology. The expression of postoperative specimens by immune-histochemical staining was used to evaluate the immune molecules ER, PR, Her-2, and Ki-67. The correlation between the ultrasound findings (size, boundary, sand calcification, and blood flow grade), as well as the expression of ER, PR, Her-2, and Ki-67 were analyzed.Results: Of the 400 cases, there were no correlations between the boundary, the classification, or the blood flow of the tumor with the expression of ER, PR, Her-2, and Ki-67. The size of tumor was correlated with Her-2 and Ki-67. The tumor is the bigger, and the expression of Her-2 and Ki-67 is higher.Conclusion: There is a correlation between tumor size and expression of Her-2 and Ki-67 in breast cancer. The combination of them was important for the treatment and prognosis of breast cancer.